1992
DOI: 10.1093/clind/15.5.799
|View full text |Cite
|
Sign up to set email alerts
|

Extraparenchymal Neurocysticercosis: Report of Five Cases and Review of Management

Abstract: Neurocysticercosis due to parenchymal cysts carries a good prognosis regardless of therapy. Extraparenchymal neurocysticercosis (including ventricular, spinal, and subarachnoid types) carries a poorer prognosis. Most extraparenchymal cases present with hydrocephalus. Medical treatment alone in doses and schedules developed for parenchymal disease is frequently unsuccessful. For ventricular disease, most cases can be managed with shunting procedures either alone or together with the administration of antiparasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
6

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 51 publications
1
66
1
6
Order By: Relevance
“…39 The best treatment-surgical or medical-in patients with giant, intraventricular, or subarachnoid forms of NCC remains unknown. 1,5,19,32,34,35 Surgical treatment, with excision of the cysticerci after laminectomy, is still indicated in cases of spinal cord or radicular compression by free cysts. In symptomatic patients with intramedullary cysts, surgery is commonly indicated for decompression of the spinal cord as well as to clarify diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…39 The best treatment-surgical or medical-in patients with giant, intraventricular, or subarachnoid forms of NCC remains unknown. 1,5,19,32,34,35 Surgical treatment, with excision of the cysticerci after laminectomy, is still indicated in cases of spinal cord or radicular compression by free cysts. In symptomatic patients with intramedullary cysts, surgery is commonly indicated for decompression of the spinal cord as well as to clarify diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][9][10][11][12][13][14]16,18,19,24,25,28) An analysis of 753 cases of neurocysticercosis found the incidence of spinal intramedullary cysticercosis to be 0.77%. 26) About 50% of patients harbored the parasite in other sites, such as the brain (30%) and muscles (25%).…”
Section: Discussionmentioning
confidence: 99%
“…4,8) Involvement of the spine is rare, ranging from 0.7-5.8%. 11,26) Involvement of spinal subarachnoid space is six to eight times commoner than the spinal cord parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with intraventricular NC (IV-NV) the medication of choice is ABZ even in HIV-positive patients . However subarachnoid neurocysticercosis (SA-NC) shows a poor response to antiparasitic medication and some authors reported not adequate response to ABZ, at all (Bandres et al, 1992;White et al, 1992;Del Brutto, 1997;Cardenas et al, 2010). Cysts in the basal cisterns can cause an inflammatory reaction, fibrosis and progressive thickening of the leptomeninges at the base of the brain.…”
Section: Treatment Failure and Its Consequencesmentioning
confidence: 99%